Poly(cytosine)‐templated Silver Nanoclusters as Fluorescent Biosensor for Highly Sensitive Detection of Uric Acid. Issue 8 (2nd August 2016) - Li, Yanle; Gong, Nianchun; Jiang, Xi; Zheng, Xiaofang; Wang, Yaya; Huan, Shuangyan
Abstract: Uric acid (UA) is an important biomarker in urine and serum samples for early diagnosis. This study re‐ ports a fluorescent biosensor based on Poly(cytosine)‐templated silver nanoclusters (C‐Ag NCs) and uricase for the highly sensitive and fast detection of UA. The strong fluorescence of the C‐Ag NCs prepared from poly (cytosine) nucleotides templates could be sensitively quenched by trace amount of H2 O2, which produced from oxidation reaction of UA catalyzed by uricase. This biosensor exhibits two linear ranges as 50 nM∼50 μM and 50 μM∼400 μM, with a detection limit of 50 nM. The sensitivity of the biosensor is considerably improved compared with the methods reported in the literature. Furthermore, the detection ability of uric acid in serum samples is confirmed and this C‐Ag NCs‐based uric acid biosensor shows good promise of practical application. Abstract : A novel fluorescent biosensor was developed for the highly sensitive and fast detection of uric acid (UA) based on Poly(cytosine)‐templated silver nanoclusters (C‐Ag NCs) and uricase, due to the strong fluorescence of the C‐Ag NCs sensitively quenched by trace amount of H2 O2, which produced from oxidation reaction of UA catalyzed by uricase.